Enterococci levels in the Bronx River during dry and wet weather conditions - Enecio,Maria Leanna; Krakauer,Nir Y. (PeerJ PrePrints, 2014)
The purpose of this project was to understand fecal microorganism contamination in the Bronx River within New York City and how it is affected by combined sewer overflow (CSO) events. Nine sites along the Bronx River were sampled throughout the summer of 2014 during wet and dry weather conditions. The samples were analyzed for enterococcus fecal indicator bacteria (FIB) concentration. The data revealed that wet weather enterococci concentrations are as 3 to 28 times greater than dry weather concentrations. The highest enterococci concentrations were found where the river enters Bronx County from Westchester County and near a storm water outfall. The positive correlation shown between the amount of rainfall and the FIB concentrations verifies that CSO and storm water discharges are a major source of FIB contamination in the river.
Keywords: Bronx River; fecal indicator bacteria; combined sewer overflow; cso; enterococci